Analisis Pelaksanaan Program Kejar Paket Tuntaskan Putus Sekolah Pada Peserta Didik Paket C di Sanggar Kegiatan Belajar Kabupaten Gresik, Jawa Timur - Anggraini, Nita Julia; Riyanto, Yatim (J+PLUS UNESA, 2023)
Non-formal education is a learning process that takes place in an organized way outside the formal education system/school, one of which is package C equivalence education. The Gresik Regency Government has provided an innovative program, namely the "Jaketku" complete drop-out program, which aims to complete out-of-school/drop-out children. The implementation of the complete dropout package chase program must of course be appropriate and right on target for people who need further education. The researcher used a qualitative descriptive method at SKB Gresik, Cerme District. The data collection used was in-depth interviews, participant observation, and documentation. The results of the study concluded that the implementation of the program to catch up on dropouts at SKB Gresik in the Cerme District was expected to actually be able to complete the children who did not go to school/dropouts in Gresik district, especially in the sub-districts which were the targets of implementing the program to catch up/education equality. As well as the hope of the community in continuing their education level which had stopped during elementary school and high school, with the hope that the people of Gresik district, especially in the Cerme sub-district, have high enthusiasm in continuing their education in adulthood and providing welfare for their lives in the future.